UJI EFEKTIVITAS RENDAMAN DAUN SINGKONG (Manihot utilissima) SEBAGAI INSEKTISIDA TERHADAP NYAMUK Aedes aegypti DENGAN METODE ELEKTRIK CAIR - Faya Azjka Iftita (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Aedes aegypti is a vector of Dengue Hemorrhagic Fever. It’s necessary to find other alternatives for vector control with a method that is more environmentally friendly. Leaves of cassava (Manihot utilissima) contains flavonoids and cyanide can be use for insecticide. Liquid vaporizer selected because free of smoke and dust.This study use an experimental method with Randomized Control Trial design. The sample in this study used Aedes aegypti females aged 3-5 days were full of sugar solution about 960 tails. In this test, performed 4 times repetition. Divided in to 5 concentration, which is 18%, 31%, 39%, 63% and 124%. Mosquitoes exposed for 20 minutes and holding for 24 hours. The sample size for each treatment used 20 mosquitoes. LC50 values obtained 47.82% and LT50 23.44 hours with a level of 95%. Result showed that the most effective concentration as electrical was 39.32%. Communities can grow cassava for controlling Aedes aegypti which is cheap andenvironmentally friendly.